Phenotypic examination of variation occurring both among families and among genotypes within a T. repens x (T. ambiguum x T. occidentale) BC₁F₂ hybrid population : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Plant Breeding at Massey University, Palmerston North, New Zealand - Slack, Stephen Charles (Massey University, 2017)
Development of white clover cultivars with increased vegetative persistence, particularly in dryland farming systems has been a major goal within breeding programmes, however little useful genetic variation for survival and growth in these environments has been found. Consequently, it has become necessary to look towards white clovers wild relatives as sources of genetic variation. T. repens x (T. ambiguum x T. occidentale) tri-species hybrids have been developed, however, their morphologies have not been evaluated, and little is known about optimal breeding strategies in these populations. An experiment was designed to characterise the magnitude of phenotypic variation for a range of root, shoot, and floral traits, and to ascertain optimal breeding strategies within a T. repens x (T. ambiguum x T. occidentale) BC1F2 hybrid plant population. The experiment was designed such that it could be analysed in two ways; a) Investigated levels of phenotypic variation occurring among hybrid families, compared to representatives of their F1 parents b) Investigated levels of phenotypic variation among individual hybrid Genotypes, again compared to representatives of their F1 parents. Analysis (a) found a relative lack of among hybrid family variation. With significant (P<0.05) family variance components for 11 of the 18 traits measured, and generally only occurring between the upper and lower extremes. Repeatability estimates on a family mean basis were low less than 0.51 for all traits). Analysis (b) found significant (P<0.05) genotypic variance components for all of the traits measured. Repeatability estimates Ranged from 0.47-0.88, indicating a relatively high level of genetic determination for the majority of traits. Pattern analysis allowed the identification of hybrid genotypes showing the combined expression of key shoot, and root traits. These genotypes may provide a route to hybrid clover cultivars showing increased vegetative persistence via increased nodal and tap-root size, combined with good dry matter production.
Keywords: White clover; Breeding; Genetics; Hybridization; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Plant production::Plant breeding